SENSITIVITY ANALYSIS OF RELIABILITY OF GEAR IN WIND TURBINE GEAR-BOX BASED ON DYNAMICS - WANG ChunGuang (Jixie qiangdu)
Main failure parts of wind turbine gear-box were determined by Failure Modes and Effects Analysis（FMEA）.Gear,rolling bearing and gear transmission system for the wind turbine reliability evaluation models were built based on dynamics.Four order moment method was adopted in contact fatigue and bend fatigue reliability sensitivity analysis of planetary gear,Gear reliability sensitivity is discussed.The results of influence of parameters on reliability of planetary gear are illustrated by a specific example.